(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Congenital heart defects (CHD) occupy a leading position in the structure of child mortality and remain one of the most common causes of perinatal mortality. CHDs represent a public health problem not only in Uzbekistan, but throughout the world. This article presents the results of a literature review of scientific research works devoted to the problem of congenital heart defects, published in domestic and foreign literature. Children with congenital heart defects (CHD) are characterized by developmental features that are based on pathology of the cardiovascular system. The type and severity of congenital heart disease, the age of correction of the defect and a number of other factors have a direct impact on the severity of its non-cardiac complications, such as disorders of physical and motor development, caused by the special conditions of the formation of the nervous system in conditions of congenital heart disease.